Kinetic, Mechanistic, and Thermodynamic Studies for Oxidation of L-Alanine by Alkaline Sodium Periodate in Presence of Os(VIII) in its Nano Concentration Range as Homogenous Catalyst - Madhu Gupta; Amrita Srivastava; Sheila Srivastava (Department of Chemical Engineering - Diponegoro University, 2018)
The kinetics and mechanism of homogenously Os(VIII) catalysed oxidation of L-alanine (L-ala) by alkaline sodium periodate in temperature range 30 to 45°C have been studied. The involvement of free radicals was observed in the reactions. The oxidation products were acetaldehyde and IO3-, identified by spot test and spectroscopic studies. The stoichiometry between [L-ala]: IO4- is 1:2. The reaction show negligible effect of mercuric acetate and ionic strength of medium. The experimental results show first order in oxidant [NaIO4] and negative effect of [OH-]. The order in [Os(VIII)] as well as L-alanine was unity. A mechanism involving the formation of complex between L-alanine and Os(VIII) was proposed. The reaction constants concerned in the different steps of mechanism were calculated at different temperature. The activation parameters for the slow step of mechanism were computed and discussed. The thermodynamic quantities were also calculated for the reaction.